Proof of Concept for Prevention of Natural Colonization by Oral Needle-Free Administration of a Microparticle Vaccine - Frandoloso, Rafael; Chaudhuri, Somshukla; Frandoloso, Gabriela Carolina Paraboni; Yu, Rong-hua; Schryvers, Anthony Bernard (Frontiers in Immunology, 2020)
There has been substantial interest in the development of needle-free vaccine administration that has led to a variety of approaches for delivery through the skin for induction of a systemic immune response. The mucosal administration of vaccines has inherently been needle-free but the simple application of vaccines on the mucosal surface by itself does not lead to mucosal immunity. Since many important bacterial infections develop after initial colonization of the upper respiratory tract of the host, prevention of colonization could not only prevent infection but also eliminate the reservoir of pathogens that reside exclusively in that ecologic niche. This study was designed to provide proof of concept for a needle-free immunization approach that would reduce or eliminate colonization and prevent infection. In order to accomplish this a microparticle vaccine preparation was delivered just below the oral mucosal epithelial cell layer where it would lead to a robust immune response. A vaccine antigen (mutant transferrin binding protein B) shown to be capable of preventing infection in pigs was incorporated into a polyphosphazene microparticle preparation and delivered by a needle-free device to the oral sub-epithelial space of pigs. This vaccination regimen not only provided complete protection from infection after intranasal challenge by Glaesserella parasuis but also eliminated natural colonization by this bacterium. Notably, the complete prevention of natural colonization was dependent upon delivery of the microparticle preparation below the epithelial layer in the oral mucosa as intradermal or intramuscular delivery was not as effective at preventing natural colonization. This study also demonstrated that a primary immunization in the presence of maternal antibody limited the resulting antibody response but a robust antibody response after the second immunization indicated that maternal antibody did not prevent induction of B-cell memory.